2015
DOI: 10.1155/2015/258589
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Therapies for Autism Spectrum Disorder

Abstract: Background. Complementary and alternative medicine (CAM) represents a popular therapeutic option for patients with autism spectrum disorder (ASD). Unfortunately, there is a paucity of data regarding the efficacy of CAM in ASD. The aim of the present systematic review is to investigate trials of CAM in ASD. Material and Methods. We searched the following databases: MEDLINE, EMBASE, Cochrane Database of Systematic Reviews, CINAHL, Psychology and Behavioral Sciences Collection, Agricola, and Food Science Source. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 135 publications
(140 reference statements)
1
66
0
2
Order By: Relevance
“…Although the duration of use and the dosage of camel milk are yet to be determined on a larger scale, it has been suggested by Al-Ayadhi and Elamin [17] that camel milk plays a crucial role in reducing oxidative stress and in the improvement of autistic behavior since individuals with ASD have shown to be vulnerable to oxidative stress. Likewise, it has also been demonstrated significant improvement in CARS following consumption of raw camel milk [14].…”
Section: Dietary Interventionsmentioning
confidence: 94%
See 4 more Smart Citations
“…Although the duration of use and the dosage of camel milk are yet to be determined on a larger scale, it has been suggested by Al-Ayadhi and Elamin [17] that camel milk plays a crucial role in reducing oxidative stress and in the improvement of autistic behavior since individuals with ASD have shown to be vulnerable to oxidative stress. Likewise, it has also been demonstrated significant improvement in CARS following consumption of raw camel milk [14].…”
Section: Dietary Interventionsmentioning
confidence: 94%
“…However, Brondino et al [14] showed no significant clinical improvement which may be due to small sample size and short duration of the intervention. The main reason put forward by parents for not using elimination diets was its high cost [14].…”
Section: Dietary Interventionsmentioning
confidence: 95%
See 3 more Smart Citations